The Implementation of the Senior High School Curriculum: A Case Study at SMA PAB 6 Helvetia - Mujahid Syarif (Yayasan Rahmat Islamiyah, 2026)
The implementation of the senior high school curriculum is a crucial aspect in determining the quality of teaching and learning processes and outcomes. The curriculum serves as the primary guideline for planning, implementing, and evaluating learning activities in schools. This study aims to analyze the implementation of the senior high school curriculum at SMA PAB 6 Helvetia. A qualitative approach with a case study design was employed. Data were collected through observations, interviews, and document analysis involving the principal, teachers, and students. The findings indicate that the curriculum implementation at SMA PAB 6 Helvetia has generally been carried out in accordance with applicable regulations, including lesson planning, instructional practices, and learning evaluation. However, several challenges were identified, such as limited facilities and variations in teachers’ competencies in implementing the curriculum effectively. Therefore, efforts to enhance teachers’ professional capacity and strengthen school management are necessary to ensure more effective and sustainable curriculum implementation.